Widely targeted metabolomics analysis reveals differences in volatile metabolites among four Angelica species - Jiaojiao Ji; Lanlan Zang; Tingting Lu; Cheng Li; Xiaoxu Han; Soo-Rang Lee; Li Wang (Natural Products and Bioprospecting)
Abstract Angelica L. has attracted global interest for its traditional medicinal uses and commercial values. However, few studies have focused on the metabolomic differences among the Angelica species. In this study, widely targeted metabolomics based on gas chromatography-tandem mass spectrometry was employed to analyze the metabolomes of four Angelica species (Angelica sinensis (Oliv.) Diels (A. sinensis), Angelica biserrata (R.H.Shan & Yuan) C.Q.Yuan & R.H.Shan (A. biserrata), Angelica dahurica (Hoffm.) Benth. & Hook.f. ex Franch. & Sav. (A. dahurica) and Angelica keiskei Koidz. (A. keiskei)). A total of 698 volatile metabolites were identified and classified into fifteen different categories. The metabolomic analysis indicated that 7-hydroxycoumarin and Z-ligustilide accumulated at significantly higher levels in A. sinensis, whereas bornyl acetate showed the opposite pattern. Furthermore, a high correspondence between the dendrogram of metabolite contents and phylogenetic positions of the four species. This study provides a comprehensive biochemical map for the exploitation, application and development of the Angelica species as medicinal plants or health-related dietary supplements. Graphical Abstract